Online Machine Learning for Energy-Aware Multicore Real-Time Embedded Systems - Hoffmann, Jose Luis Conradi; Frohlich, Antonio Augusto (IEEE transactions on computers, 2022)
In this article, we present an Online Learning Artificial Neural Network (ANN) model that is able to predict the performance of tasks in lower frequency levels and safely optimize real-time embedded systems' power saving operations. The proposed ANN model is supported by feature selection, which provides the most relevant variables to describe shared resource contention in the selected multicore architecture. The variables are used at runtime to produce a performance trace that encompasses sufficient information for the ANN model to predict the impact of a frequency change on the performance of tasks. A migration heuristic encompassing a weighted activity vector is combined with the ANN model to dynamically adjust frequencies and also to trigger task migrations among cores, enabling further optimization by solving resource contentions and balancing the load among cores. The proposed solution achieved energy-savings of 24.97 percent on average when compared to the run-to-end approach, and it did it without compromising the criticality of any single task. The overhead incurred in terms of execution time was 0.1791 percent on average. Each prediction added 15.3585 μ s μs<inline-graphic xlink:href="conradihoffmann-ieq1-3056070.gif"/> on average and each retraining cycle triggered at frequency adjustments was never larger than 100 μ s μs<inline-graphic xlink:href="conradihoffmann-ieq2-3056070.gif"/> .